PENGARUH FASILITAS IPSRS, MELALUI KEPUASAN KERJA, TERHADAP KINERJA NAKES RSUD J.P. WANANE SORONG - Krytlaan H. Kantohe; Satrya Bayu Irawan (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the effect of work facilities on worker performance through job satisfaction at J.P. Wanane Sorong Regional Hospital. This study used a survey method with a sample of 30 health workers (Nakes) representing various job groups. Data were analyzed using the SmartPLS v.3 method with the results of the study showing that IPSRS work facilities have a significant positive effect on job satisfaction; IPSRS facilities have an insignificant positive effect on Nakes performance; job satisfaction has an almost significant positive effect on Nakes performance; and finally IPSRS facilities through job satisfaction have an insignificant positive effect on Nakes performance. This means that improving IPSRS facilities, although increasing job satisfaction, has not played a role in improving Nakes performance. It is hoped that, although not yet significant in the span of this study, the maintenance and renewal of IPSRS facilities will continue to be improved in order to improve job satisfaction and Nakes performance.